Mel de Apis mellifera como bioindicador de resíduos de pesticidas - Cunha, Fernando da (2016)
The direct and indirect effects of agricultural pesticides has been the focus of increasing numbers of studies by different entities and in different locations. The Apis mellifera bee is an insect that are part of the natural environment, producing honey from its interaction with vegetation. Brazilian legislation seldom refers to the concentration of pesticides in food, and honey, a product produced by bees, has had few cases of contamination by pesticides used for the control of pests in agriculture. The maximum pesticide residue limit (MRLs) established in legislation principally relate to those products used in large-scale crop production. Organophosphate and organochloride standards were used on samples and validated. In this way the identification of pesticide residues in honey generated by bees acquired in native trees and planted cultures in a 1,500m radius of the hives, by way of chromatography (CGMS), was estimated over two seasons in fifteen apiaries in the city of Santa Helena-PR. On average, the areas utilised for the study corresponded to 58.92% under agricultural production, 22.08% in native forest, 9.52% in water, and 6.04% in buildings and dwellings. There was however no significant effect in the study area on the percentage of contamination in the samples. In september to november of 2013, 26.66% of the samples were contaminated. In december to january of 2014 the figure was 8.88%. There was significant effect in the period (p<0.05) on the Fenclorfós, Chloropyrifos, Mitotane and Bicylo, with a greater occurrence and concentration in september to november of 2013. Those pesticides with residue limits outside of the legislation, did not have significant effect in the period (p>0.05) on the occurrence of contaminated samples with Parathion Methyl, Chloropyrifos, and DDE. Parathion Methyl and Chloropyrifos were found at levels above those specified in the legislation in both periods of the study. This would suggest the overuse of these pesticides at above recommended levels by agricultural producers to control pests. In conclusion, the Apis mellifera bees were efficient in the detection of pesticide residues in honey, that were used in agricultural production near the apiaries between September 2013 and December 2014. This reinforces the potential of these insects as bioindicators of environmental quality